2013
DOI: 10.1111/vox.12065
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial culture of apheresis platelets: a mathematical model of the residual rate of contamination based on unconfirmed positive results

Abstract: Greater than 99·5% of collections contain no viable, aerobic bacteria in solution at the time of early culture testing. For every confirmed positive contaminated collection detected, there are at most 19 collections with low concentrations of dormant bacteria that are not readily detected by early BacT/ALERT™ culture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
88
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(91 citation statements)
references
References 20 publications
3
88
0
Order By: Relevance
“…Despite the availability of bacterial detection methods, bacterial contamination of PCs still poses the highest risk of transfusion‐transmitted disease . Bacteria can be missed in early testing due to low bacterial concentrations.…”
mentioning
confidence: 99%
“…Despite the availability of bacterial detection methods, bacterial contamination of PCs still poses the highest risk of transfusion‐transmitted disease . Bacteria can be missed in early testing due to low bacterial concentrations.…”
mentioning
confidence: 99%
“…The probability of bacterial detection with primary culture is a function of the input volume, timing of testing relative to collection, the size of the bacterial inoculum, and the kinetics of bacterial growth for the implicated organism itself. The latter can be slow growing, thus escaping early detection at the blood collection center . By increasing the time relative to collection, secondary bacterial culture optimizes the probability of detection.…”
Section: Discussionmentioning
confidence: 99%
“…(3 cases) [5]. Benjamin et al [14] examined bacterial culture of platelet products free from antibodies and found the same bacterial species that are associated with sepsis [14]. …”
Section: Discussionmentioning
confidence: 99%